Biometrics and Identity Management - David Hutchison, Takeo Kanade, Josef Kittler, Jon M. Kleinberg, Friedemann Mattern, John C. Mitchell, Moni Naor, Oscar Nierstrasz, C. Pandu Rangan, Bernhard Steffen, Madhu Sudan, Demetri Terzopoulos, Doug Tygar, Moshe Y. Vardi, Gerhard Weikum, Ben Schouten, Niels Christian Juul, Andrzej Drygajlo, Massimo Tistarelli. (Springer, 2017)
268 p.